Аналитическое определение установившегося температурного поля в обмотке ротора с учетом вытеснения тока в пазу асинхронного электродвигателя с короткозамкнутым ротором - Гусаров, Алексей Андреевич; Ковалев, Евгений Борисович (НТУ "ХПИ", 2009)
С использованием теории электромагнитного поля для плоской линейной поляризованной волны, приводятся аналитические исследования распределения температуры в обмотке ротора асинхронных электродвигателей в стационарных режимах с учетом вытеснения тока.

With application of theory of electromagnetic field for a flat linear polarized wave, analytical research into temperature distribution in the rotor winding of asynchronous motors is done for stationary modes with allowance for current displacement.
Analytical determination of steady-state temperature field in a rotor winding subject to current displacement in the slot of an asynchronous short-circuited motor
Keywords: теория электромагнитного поля; литые алюминиевые обмотки; стационарный режим; напряженность поля; flat polarized wave; slot heating; temperature distribution; current displacement; stationary mode; asynchronous motor